Determinants of Indonesia's Coal Export Value to Five Main Destination Countries for the 2009-2023 Period - Ni Kadek Wiwin Andari; I Nyoman Wahyu Widiana (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
As a developing country that adheres to an open economic system, Indonesia is inseparable from international trade, one of which is exports. Indonesia's leading export in non-oil and gas commodities is coal. The value of Indonesia's coal exports to five destination countries from 2009-2023 continues to fluctuate. The purpose of this study is to analyze the simultaneous and partial effects of reference prices, total consumption, and renewable energy on the value of Indonesia's coal exports to five main destination countries for the period 2009-2023. The number of observations in this study was 75 observations. This research method uses descriptive analysis techniques and panel data regression. The results of the regression test on panel data show that the most appropriate model is FEM. The results of this study indicate that the variables of reference price, total consumption, and renewable energy simultaneously have a significant effect on the value of Indonesia's coal exports. Partially, the variables of reference price and total consumption have a positive and significant effect, while renewable energy has a negative and significant effect on the value of Indonesia's coal exports.